Myotonia congenita in a young active man: Symptoms and physique tip the diagnosis - Chew, K. T. L.; Wong, Y. -S.; Teoh, H.-L.; Lim, E. C. H. (The Physician and Sportsmedicine, 2004)
A 19-year-old man had a 7-year history of leg cramps and a tendency for his legs to "seize up" when he participated in sports. The condition was initially mild, and clinical examination revealed an extremely muscular physique and percussion and action myotonia. Electromyography was consistent with myotonic discharges, and myotonia congenita was the diagnosis. Carbamazepine therapy relieved all symptoms, except for a short time when the patient stopped taking medication. Physicians should carefully document family history and symptom triggers to facilitate making the correct diagnosis.